2010
DOI: 10.1210/jc.2009-2608
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Profile Heterogeneity and Short-Term Physical Risk in Restrictive Anorexia Nervosa

Abstract: The hormonal response to undernutrition is heterogeneous in a large population with restrictive AN. In clinical practice, metanephrines, GH, and/or cortisol data could be used as important predictors for severe short-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 32 publications
6
64
0
Order By: Relevance
“…As demonstrated by Dos Santos et al (21), female rats submitted to treadmill exercise and a 50% food restriction led to interruption of estrous cyclicity, as we observed in our study where the physical activity was voluntary. In AN patients, even if amenorrhea was not considered as a criterion in the DSM-5 anymore, disruption of cycles is currently observed in restrictive AN patients (24,42). Disruption of the estrous cycle as well as reduction of the size of ovaries was observed here in FR and FRW mice along all the protocols.…”
Section: E252 Chronic Food Restriction and Physical Activitymentioning
confidence: 69%
See 2 more Smart Citations
“…As demonstrated by Dos Santos et al (21), female rats submitted to treadmill exercise and a 50% food restriction led to interruption of estrous cyclicity, as we observed in our study where the physical activity was voluntary. In AN patients, even if amenorrhea was not considered as a criterion in the DSM-5 anymore, disruption of cycles is currently observed in restrictive AN patients (24,42). Disruption of the estrous cycle as well as reduction of the size of ovaries was observed here in FR and FRW mice along all the protocols.…”
Section: E252 Chronic Food Restriction and Physical Activitymentioning
confidence: 69%
“…In AN, patients also display numerous endocrine alterations that can contribute directly or indirectly to maintain and exacerbate the disease (24,66). Data related to the understanding of how hormones might contribute to the worsening of the patients are currently lacking.…”
Section: E249 Chronic Food Restriction and Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters related to nutritional status including IGF-1, free T3, leptin and percentage of fat mass were assessed in BN group using previously described techniques (Estour et al 2010).…”
Section: Nutritional Profi Le Assessmentmentioning
confidence: 99%
“…The present study revealed an inverse association between baseline cortisol AUC level and SD for body weight, indicating that higher basal cortisol secretion could be indicative of severity of illness. Estour's large cohort study (210 young females with AN) suggested that cortisol could be used as an important prognostic predictor, with increased levels of cortisol in AN patients who developed critical states during the 3 months (Estour et al, 2010). The HPA axis is essential for maintaining homeostasis in stress processing and adaptation to the environment, thus cortisol is used as a biomarker of psychological stress and related mental or physical disease (Hellhammer et al, 2009;Sjörs et al, 2010).…”
Section: Discussionmentioning
confidence: 99%